2019
DOI: 10.3389/fcell.2019.00320
|View full text |Cite
|
Sign up to set email alerts
|

Considering the Role of Murine Double Minute 2 in the Cardiovascular System?

Abstract: The E3 ubiquitin ligase Murine double minute 2 (MDM2) is the main negative regulator of the tumor protein p53 (TP53). Extensive studies over more than two decades have confirmed MDM2 oncogenic role through mechanisms both TP53-dependent and TP53-independent oncogenic function. These studies have contributed to designate MDM2 as a therapeutic target of choice for cancer treatment and the number of patents for MDM2 antagonists has increased immensely over the last years. However, the question of the physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 144 publications
(227 reference statements)
1
7
0
Order By: Relevance
“…All these beneficial effects of JNJ-165 were reduced by the transfection of RXRβ siRNA, but not p53 siRNA. In line with our results, there is a notion that beyond the primary function of MDM2 to keep p53 under control, MDM2 has functions that are independent of p53 in vascular cells such as endothelial cells, vascular smooth cells and cardiomyocytes [ 16 ]. Moreover, the in vivo experiment in the present study for the first time showed that MDM2 inhibitor JNJ-165 alleviated the development of atherosclerosis and reversed mitochondrial damage and related inflammation in this process, along with the increased RXRβ protein expression in the aorta of mice.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…All these beneficial effects of JNJ-165 were reduced by the transfection of RXRβ siRNA, but not p53 siRNA. In line with our results, there is a notion that beyond the primary function of MDM2 to keep p53 under control, MDM2 has functions that are independent of p53 in vascular cells such as endothelial cells, vascular smooth cells and cardiomyocytes [ 16 ]. Moreover, the in vivo experiment in the present study for the first time showed that MDM2 inhibitor JNJ-165 alleviated the development of atherosclerosis and reversed mitochondrial damage and related inflammation in this process, along with the increased RXRβ protein expression in the aorta of mice.…”
Section: Discussionsupporting
confidence: 84%
“…MDM2 is involved in many important biological processes. In addition to its well-known tumorigenic characteristics by impacting p53, MDM2 is also reported to be involved in the pathophysiological events of the cardiovascular system [ 16 , 17 , 18 , 19 , 20 ]. Our previous study has indicated that MDM2 contributes to ox-LDL-induced activation of the TLR9/NF-κB pathway and NLRP3/caspase-1 inflammasome through modulation of mitochondrial damage in endothelial cells [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our model predicted that it decreased DNA synthesis activity. MDM2 plays a diverse role in the cardiovascular systems, and studies to elucidate its interaction with upstream and downstream regulators are needed (Hauck et al, 2017; Lam & Roudier, 2019; Stanley-Hasnain et al, 2017). The majority of the incorrect predictions involved output responses for the polyploid phenotype.…”
Section: Discussionmentioning
confidence: 99%